High-dependency unit care after carotid endarterectomy for asymptomatic stenosis - Guimarães, Beatriz (2025)
INTRODUCTION: Asymptomatic patients benefit from 3 to 6 hours of neurological and invasive blood pressure (BP) monitoring following carotid endarterectomy (CEA). Only a minority of patients will benefit from a prolonged stay in a high-dependency unit (HDU). The aim of this study was to externally validate previously described predictive variables of postoperative need for prolonged HDU stay. METHODS: To identify patients needing HDU stay, a composite outcome (CO) was created, including cardiac events, neurologic deterioration, postoperative aminergic/ventilatory support, and prolonged use of intravenous (IV) BP control therapy. A retrospective study was performed in one center: increased clamping time, preoperative systolic BP, systolic BP during pre-anesthetic procedure, maximum intraoperative mean arterial pressure (MAP), and eversion technique were significant predictors for the CO. We aimed to ascertain the validity of these factors in an independent population. Consecutive patients submitted to asymptomatic CEA in the same period were retrospectively analyzed in a second independent center. RESULTS: A total of 51 procedures were included (86.3% male; 69.2±7.9 years) and 11 (21.6%) presented with the CO. The presence of diabetes was associated with a higher incidence of the CO (p=0.011), and acetaminophen as intraoperative analgesia demonstrated an inverse correlation with the CO (p<0.001). Receiver operator characteristic curve analysis of predictive factors revealed that intraoperative maximum MAP had a strong correlation with the CO (area under the curve – AUC – 0.739, p=0.017). The remaining variables also did not reach statistical significance. CONCLUSIONS: In this analysis, the risk for CO development was consistently increased in patients who developed high MAP intra-operatively, highlighting the need for scrupulous BP management to reduce potential complications. However, we identified two previously unidentified associations: first, diabetics were more prone to develop complications and were more likely to benefit from HDU stay. Second, acetaminophen as intraoperative analgesia could have a protective role against CO development.